COLLEGE STUDENTS’ PERCEPTION OF SCHOOLOGY IN COMPUTER ASSISTED LANGUAGE LEARNING COURSE - nugroho nugroho (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2020)
This study aims to determine the perceptions of students as prospective teachers of Schoology in Computer Assisted Language Learning subjects. Schoology is a web-based learning media commonly called the Learning Management System. Schoology is one of the free web platform in the form of social web and easy to use like Facebook. This study uses a qualitative descriptive method and approach with data collection methods in the form of interviews. The interviewer interviewed nine informants, sixth semester students in Computer Assisted Language Learning subjects with a Schoolgy discussion. Informants acted as instructors in their groups randomly selected. The results of the interview show that all informants already know the schoology and its features. Informants will also use schoology when they become teachers. The obstacle faced by 44% of students is when making material in the form of quizzes. They usually forget to arrange the quiz so the quiz does not appear on the student account. Another obstacle is to download the value and print it. But overall the students' perceptions of schoology in Assisted Language Learning courses are good. This research will be developed at the school level, Schoology in the view of teachers and students.